Venous gas in the intrahepatic portal in an obstetric patient with preeclampsia: a case report - Carlos Mendiola-Villalobos; María del Carmen García-Pantoja; Ignacio Rodríguez-Guevara; Marian Elizabeth Phinder-Puente; Nora Noemí Hernández Velázquez; Orlando R. Pérez-Nieto; Ernesto Deloya-Tomas; Raúl González-Toribio; Christian Alberto Herrera Venegas (Journal of Medical Case Reports)
Abstract Background Preeclampsia is a severe pregnancy-related disorder associated with significant maternal and fetal morbidity. Its novelty in this case lies in the rare postdelivery complications of hepatic portal venous gas and emphysematous gastritis, conditions not previously linked to preeclampsia. Case presentation We report the case of a 37-week-and-5-day pregnant Hispanic woman of Mexican origin (Gravida 2, Para 1) presenting with severe preeclampsia and hemolysis, elevated liver enzymes, and low platelets syndrome. She underwent an emergency cesarean section due to severe-range hypertension that did not spontaneously resolve. Postdelivery, the patient developed hepatic portal venous gas and emphysematous gastritis. These findings were confirmed through diagnostic imaging, including a computed tomography scan, which showed intrahepatic gas and air within the gastric wall. Despite these findings, the patient remained clinically stable. Conservative management, including supportive care and close monitoring, was implemented, leading to gradual improvement over several days. The patient was discharged in good condition, without further complications. Conclusions This case underscores the need for awareness of rare complications, such as hepatic portal venous gas and emphysematous gastritis, in postpartum patients with preeclampsia. A thorough evaluation, including workup for alternative diagnoses such as acute fatty liver of pregnancy, is essential. Early recognition and tailored management are crucial to ensuring favorable outcomes in such rare clinical scenarios.